How to do a teaching and research project for a tenure-track position - Cabrera-Méndez, Marga (Infonomy, 2024)
A compilation of materials necessary to prepare a competitive examination for tenured university professor is presented. Its interest lies in the fact that neither in the ministry nor in universities does there seem to be a regulation or instructions to carry out the teaching and research project. The references and materials presented here will help those faced with this task.